Identification of Pathogenic Bacteria from Striped Catfish (Pangasionodon hypophthalmus) kept in Aquaculture Ponds - Tamba, Jaya Maruli; Syawal, Henni; Lukistyowati, Iesje (Faculty of Fisheries and Marine, Universitas Riau, 2021)
Koto Masjid Village is the largest production center in striped catfish fish farming activities in Riau Province. One of the inhibiting factors is the disease caused by bacteria, this study aims to determine the types of pathogenic bacteria that have the potential to infect striped catfish. This research was conducted in August - November 2019, samples of striped catfish used in the study amounted to 15 tails with an average length of 15-25 cm taken from 5 ponds in Kampung II, Koto Masjid Village, XIII Koto Kampar Subdistrict, and then identified bacteria by Conventional Laboratory in Fish Parasites and Diseases, Faculty of Fisheries and Marine, Riau University, Pekanbaru. This study uses a survey method that is by taking samples from the field in Pu and then the isolation of bacteria is carried out from the kidney organ in the TSB media then purified on the TSA media. The results of the study found 3 types of pathogenic bacteria namely Aeromonas sp., Edwardsiella sp., and Pseudomonas sp. Water quality during the study was pH 6.6-70, DO 4.05-4.35 mg/L, NH3 0.035-0.2 mg/L and Temperature 28-300C.